Development of Thin Layer and High Performance Liquid Chromatographic Methods for The Analysis of Colourings Substances Used in the Printing Inks - Yenidogan, Semiha; Oktav, Mehmet; Ulgen, Mert (Asian Journal of Chemistry, 2010)
In the present study, a thin layer chromatography (TLC) and a reverse phase high performance liquid chromatographic (HPLC) separation methods were developed for the commercially available azo derivative pigments ie PR1 (pigment red 1), PR2 (pigment red 2), PR5 (pigment red 5), PO5 (pigment orange 5) and PY1 (pigment yellow 1) and also for the azo derivative dyes i.e., 1-[(4-chlorophenyl)azo]-2-naphthalenol (D1), ethyl 4-[2-hydroxy-1-naphthyl)azo]benzoate (D2) and 1-[(2,4,6- tribromophenyl)azo]-2-naphthalenol (D3) together with their potential reduction/degradation products, aromatic primary amines. In addition, three different commercial ink preparations contanining PR2, PR5 and PO5 were analyzed by using these developed HPLC system following solvent extraction. Compounds were separated by a thin layer chromatography system employing plastic backed silica gel adsorbents and various solvent system combinations consisted of petroleum ether, acetone, chloroform, dichloromethane and methanol. The reverse phase HPLC system was consisted of a mobile phase of acetonitrile:water (67:33, v/v) and a Zorbax Eclipse XDB-C8 column (4.6 × 150 mmlong) and it was delivered at a flow rate of 1 mL/min. The detection was carried out at a maximum wavelength of 220 nm.